Determinants of Health and Performance in Wildland Firefighters: A Narrative Review - Fabio García-Heras; Jorge Gutiérrez-Arroyo; Juan Rodríguez-Medina; Belén Carballo-Leyenda; Pilar Sánchez-Collado; Gerardo Villa-Vicente; Jose A. Rodríguez-Marroyo (Journal of Functional Morphology and Kinesiology)
Background/Objectives: Wildland firefighters (WFFs) are subjected to significant physical and physiological demands that expose them to substantial occupational risks, including thermal stress, prolonged physical exertion, and exposure to harmful substances. These factors not only affect their immediate performance but also have long-term implications for their health. This narrative review seeks to analyze the main factors influencing the health and performance of WFFs, with a particular focus on physical, environmental, and psychological challenges. Methods: A narrative review was performed, synthesizing data from diverse sources. The analysis centered on studies addressing the physiological, environmental, and psychological aspects of WFF performance. Specific topics included physical workload, exposure to environmental stressors, use of protective equipment, hydration, sleep patterns, and mental health. Results: The review highlights several critical challenges faced by WFFs, including the extreme physical demands of carrying heavy equipment during extended interventions, elevated physiological strain induced by protective gear, and significant health risks associated with smoke inhalation and dehydration. Additionally, inadequate sleep and heightened mental stress were found to impair both cognitive and physical performance. Variations in injury prevalence and patterns of chronic pain were observed, often influenced by factors such as sex, age, and professional experience. Conclusion: To mitigate these risks and enhance the health and performance of WFFs, targeted interventions are essential. These include tailored physical training programs, heat acclimatization strategies, and improved resource management. Future research should aim to integrate these measures comprehensively and address existing knowledge gaps to ensure the long-term well-being of these professionals.